Needs Analysis for the Development of a Balanced Literacy Approach Model for Beginning Reading in Elementary Schools - Septia Sugiarsih; Suhardi Suhardi; Kastam Syamsi; Albi Anggito (FKIP - Universitas Riau, 2026)
This study aims to identify the needs for developing a Balanced Literacy Approach (BLA) model to improve beginning reading instruction in elementary schools. The research was conducted in three public elementary schools in Sentolo District, Kulon Progo, involving 15 lower-grade teachers, Grade II students, and instructional documents used in the schools. Using a descriptive method within the preliminary phase of the Borg & Gall R&D model, data were collected through document analysis, classroom observations, teacher questionnaires, interviews, and an early reading test. The findings indicate that instructional documents were still general in nature and not tailored to the specific needs of early literacy development. Classroom practices were dominated by lecture-based activities and round-robin reading, with limited use of shared reading, guided reading, or independent reading. Teachers reported challenges in guiding students to understand texts and identified the lack of engaging reading materials such as Big Books. Students showed low reading interest, and test results revealed disparities between technical decoding skills and reading comprehension. These results highlight the urgent need for a structured, engaging, and applicable instructional model. The Balanced Literacy Approach is considered relevant to provide systematic, meaningful, and developmentally appropriate reading experiences for early grade learners.